PEMBERIAN HAK GUNA BANGUNAN DI ATAS BAGIAN TANAH HAK PENGELOLAAN - Triadi Kurniawan (Keadilan : Jurnal Fakultas Hukum Universitas Tulang Bawang, 2020)
The granting of Building Utilization Rights above the Management Rights land in the construction of Metro Mega Mall in Metro Lampung City raises problems, namely the legal consequences that arise in the cooperation agreement made by the Regional Government of Metro City and PT. Nolimax Jaya. The main focus of the research is the legal consequences that arise on the implementation of granting rights to build on land with management rights and the concept and application of appropriate and fair laws in the context of carrying out the transfer of management rights of the Regional Government to third parties by providing Building Use Rights certificates. This research uses non doctrinal method. The results showed that the legal effect that emerged in the granting of HGB over HPL was a temporary transfer of ownership to existing land and buildings which resulted in PT. Nolimax Jaya as a company that wants to make a profit, in addition to harming traders who want to open a business in the area. Keywords : Land Management Rights, Building Rights, Agreement.